2017
DOI: 10.1080/13854046.2017.1400105
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological feedback services improve quality of life and social adjustment

Abstract: These findings suggest that there is benefit for the individuals who chose to engage in feedback sessions. Feedback sessions can be utilized to assist with integral decision-making processes and assisting in treatment planning among other areas. It also allows time for patients and family members to discuss their concerns regarding important test findings and recommendations. Given the current climate of value-based services and clinical outcomes, the findings from this study lend support to the utility of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Given that research has identified low adherence rates to neuropsychological testing recommendations in multiple sclerosis (38%), it may be preferable to provide additive follow-up care (in-person feedback and case management) where possible, to improve compliance and increase utility for such an intervention. 14,31,35,36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that research has identified low adherence rates to neuropsychological testing recommendations in multiple sclerosis (38%), it may be preferable to provide additive follow-up care (in-person feedback and case management) where possible, to improve compliance and increase utility for such an intervention. 14,31,35,36…”
Section: Discussionmentioning
confidence: 99%
“…13 The present study sought to fill this gap by comparing a standard care intervention (neuropsychological assessment with phone feedback of recommendations) with the inclusion of additive follow-up procedures (in-person feedback and case management), as these have been efficacious in improving adherence to non-medication treatment recommendations in other illness populations. 14,15 Given that women with multiple sclerosis are at a higher risk for loss of employment, the present intervention specifically targeted employed women. 9…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that providing the patient and family with extensive feedback on the neuropsychological findings was not a universal service in Dutch MCs (Gruters et al, 2019). However, providing patients with feedback on their cognitive performance was shown to lead to improved quality of life and social adjustment (Rosado et al, 2018). Other studies have also shown that patients evaluated the feedback they received from the neuropsychologist as useful (Bennett-Levy et al, 1994;Postal & Armstrong, 2013;Westervelt et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Adherence to treatment recommendations is likely beneficial to people with MS as with other populations, 15 but data are insufficient. In addition, although the literature indicates that oral feedback is beneficial for patients and improves adherence, [16][17][18][19] it is unknown whether written and/or oral feedback leads to better adherence to treatment recommendations in people with MS.…”
Section: Methodsmentioning
confidence: 99%